Case report: Somatic mutations in microtubule dynamics-associated genes in patients with WNT-medulloblastoma tumors - Skitchenko, Rostislav; Dinikina, Yulia; Smirnov, Sergey; Krapivin, Mikhail; Smirnova, Anna; Morgacheva, Daria; Artomov, Mykyta (Frontiers in Oncology, 2023)
Background: The WNT subtype of medulloblastoma (MB) has been well described in terms of clinical, histological and genetic characteristics. Here we present two cases of WNT MB with typical clinic and atypical genetic background, carrying somatic mutations in microtubule dynamics associated genes. Methods: Two patients with WNT MB were enrolled in the study during the initial hospitalization. DNA samples were obtained from blood and tumor through surgical procedures. Exome sequencing and somatic variant calling were performed. Results: We observed two cases of MB with a histological pattern consistent with desmoplastic/nodular (DP) and classic MB, and genetically classified as WNT-MB. Both cases showed putative causal somatic protein truncating mutations identified in microtubule-associated genes: ARID2, TUBB4A and ANK3. ANK3 is a very conservative gene known to promote cancer cell invasion and metastasis. Consistently, the patient with ANK3 variant presented with metastasis. Conclusion: Somatic mutations in genes associated with microtubule dynamics can determine the clinical presentation of WNT MB.